Melampaui Pusat: Jaringan Periwayatan Hadis dan Keberagaman Geografis dalam Genre Al-Arbaʿūn al-Buldāniyyah - Muhammad Akmaluddin; Nur I'anah (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2025)
The type of arba‘ūn (forty) hadith books began to increase in quantity and variety after the 5th century AH/11th century AD. For example, there is a genre of arba‘ūn hadith that contains 40 hadiths related to their place of origin, their teachers, and the place where they narrated the hadith called al-arba‘ūn al-buldāniyyah. Research on al-arba‘ūn al-buldāniyyah is still largely focused on the work of Yāsīn al-Fādānī related to the method, takhrīj of hadith, and its comparison with other books. In addition, the study of al-arba‘ūn al-buldāniyyah shows an even pattern of narration in central and peripheral areas that needs to be studied and considered. This study will discuss how the writing method and the scientific network of hadith in al-arba‘ūn al-buldāniyyah. The practice of narrating and writing hadith from the major traditions (Makkah-Medina and other centers such as Khurasan, Iraq, Nishapur, Sham, and other peripheral areas) converges to be narrated in al-arba‘ūn al-buldāniyyah, which is a response from the authors to the shared tradition (core aspects) in hadith studies. These three books of al-arba‘ūn al-buldāniyyah function as a geographical map of hadith narration that illustrates how vast and vibrant the post-canonical hadith network is. The phenomenon of living hadith in searching for a narration network is no longer focused on the central region, but extends to peripheral areas that are no longer considered as marginal traditions, faced with the major tradition, but are equally as traditions worthy of consideration.